STUDI PADA MAHASISWA: KARAKTERISTIK, PENGETAHUAN, DAN POLA KONSUMSI TERHADAP MAKANAN SEHAT DAN HALAL - Rasmikayati, Elly; Wiyono, Sulistyodewi Nur; Saefudin, Bobby Rachmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Developing knowledge about healthy and halal food can help individuals choose the type of food that suits their nutritional and health needs. However, even though knowledge on this matter has grown rapidly, there are still many challenges in applying this knowledge in everyday life. The purpose of this study was to determine the relationship between knowledge regarding healthy and halal food and consumption patterns. The data used in this study are secondary data obtained through the results of the questionnaire. The data analysis technique used is a nonparametric statistical test including the Chi-Square test with representation using cross tabulation. The results of this study indicate that respondents understand healthy foods as foods that are slightly processed, foods that contain little sugar, flour, and carbohydrates, and foods that predominantly contain vegetables and fruits. Furthermore, respondents understood that halal food is processed food that contains additional ingredients that have been approved by the government because there is a safe quality label and food that has received a halal certificate is listed on the label. The next result is that there is no significant relationship between knowledge of halal and healthy food and consumption patterns (Breakfast, Lunch and Dinner).